Deconstructing women's double burden that returned to work during the COVID-19 pandemic - Ilise Feitshans (Oswaldo Cruz Foundation, Health Law Program, 2023)
The double burden for women has returned during the COVID-19 pandemic. As a result of the pandemic, an unprecedented percentage of women have lost their jobs or are working from home. The COVID-19 pandemic has brought back a centuries old burden, which adds to the many other burdens women face regularly - the homework burden -, that is engaging in piecework and childcare at the same time. Mapping the laws and the legal determinants of women's health disparities must be undertaken to stem the tide of this new wave of the feminization of poverty.  Guest author